Add: 3p2q2 - 4pq + 5, - 10 p2q2, 15 + 9pq + 7p2q2

3p2q2 – 4pq + 5, – 10 p2q2, 15 + 9pq + 7p2q2

Answer

On combining the like terms and adding them we get

= 3p2q2 – 4pq + 5 + (- 10p2q2) + 15 + 9pq + 7p2q2

= 3p2q2 – 10p2q2 + 7p2q2 – 4pq + 9pq + 5 + 15

= p2q2 (3 -10 + 7) + pq (-4 + 9) + (5 + 15)

= p2q(0) + pq (5) + 20

= 5pq + 20

Was this answer helpful?

 
   

0 (0)

(0)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question